EFFICACY OF HARM-REDUCTION THERAPY IN REDUCING ALCOHOL-RELATED PROBLEMS AMONG UNDERGRADUATES IN OWERRI, NIGERIA - Ann U. Madukwe; Ikeoha I. Iwuh; Nkwams C. Uwaoma; Juliana C. Njoku (European Scientific Journal, ESJ, 2015)
This study examined Harm-Reduction Therapy (HRT) as a technique in controlling Alcohol-Related Problems (ARPs). It was hypothesized that there will be a significant reduction in the occurrence of ARPs at each interval test following baseline occurrence. The second hypothesis compared the outcome for the participants in HRT and the control group. 28 male undergraduate students of Imo State University, who abuse alcohol, were selected using purposive and convenience sampling methods. Their age range was between 22-24years with a mean age of 22.96 (STD= .88). The Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) was used to screen participants for alcohol abuse, while the Alcohol drinking Consequences Questionnaire (ADCQ) was used to assess their alcoholrelated problems. The study employed an experimental design and data was generated by assessing participants’ alcohol-related problems at baseline, 30th day and 60th day of therapeutic interventions. The repeated measures analysis of variance statistics with SPSS version 17 was used for data analysis. As was hypothesized, there was an increased reduction in alcoholrelated problems among participants across test intervals. The result also showed a significant difference in the reduction of alcohol-related problems between participants in the control group and the harm-reduction therapy group only. It was concluded that harm-reduction therapy alone is effective in controlling alcohol-related problems (ARPs) among undergraduates. In addition, a recommendation for the benefit of the inclusion of the harmreduction therapy in the Nigerian public health policy was made.